Waste activated carbon transformed to electrode of supercapacitor through combining with Co(OH)2. (20th January 2021) - Xu, Cheng; Chen, Yong; Ma, Yannan; Huang, Jiandi; Zhao, Jiang; Xu, Hui
Highlights: After adsorbing MB, the waste AC combined with Co(OH)2 are successfully used as the electrode of supercapacitors. The contact angle of AC before and after adsorbing MB varies from 100.9° to 0°, suggesting that the surface properties of AC are changed from hydrophobic and hydrophilic due to adsorbing MB. A light-emitting diode can be lit by the symmetric supercapacitor based on AC/MB/Co(OH)2 composites. The idea of developing the waste into new energy is feasible. Abstract: Activated carbon (AC) is a multifunctional material. On the one hand, it is used as adsorbent to remove pollutants in wastewater, on the other hand, it is a preferred electrode for supercapacitors. Herein, we fabricate a hybrid electrode based on Co(OH)2 and waste AC which is supposed to discard after removing methylene blue (MB) from water. Scanning electron microscopy (SEM), X-ray diffraction (XRD), and X-ray photoelectron spectroscopy demonstrate AC/MB/Co(OH)2 nanocomposites are successfully synthesized via precipitation method. Furthermore, the specific surface area of AC/MB/Co(OH)2 is dramatically improved compared to Co(OH)2 . Cyclic voltammetry (CV), galvanostatic charge-discharge (GCD), and electrochemical impedance spectrum (EIS) tests suggest that the specific capacity of AC/MB/Co(OH)2 is 447 C g -1 at a current density of 1 A g -1 in 3M KOH, which is higher than that of Co(OH)2 (329 C g -1 ) or AC/Co(OH)2 (347 C g -1 ). The result indicates that MB adsorbed on AC can provide pseudo-capacity for the hybrid electrode. The assembled asymmetric supercapacitor has a power density of 400 W kg -1 at an energy density of 18 Wh kg -1 and can power a light emitting diodes (LED) easily. Thus, this strategy makes it possible to further use waste AC as the electrode of supercapacitor, which avoids secondary pollution that comes from the adsorbents.